Struma Ovarii with Papillary Thyroid Carcinoma - Alvarez, Daniel M. (Medknow Publications & Media Pvt Ltd, 2011)
Struma ovarii is an uncommon condition, in which thyroid tissue is the predominant or exclusive element in an ovarian teratoma. Thyroid tissue may demonstrate the same spectrum of pathological features as in the normal thyroid including benign and malignant changes. We present a case of papillary thyroid carcinoma arising in a struma ovarii of the left ovary in a 21-year-old female.